Continuance intention of using ebook among higher education students - I., Tri-Agif; A., Noorhidawati; S. Ghazal, Ghalebandi; Tri-Agif, I.; Noorhidawati, A.; Ghalebandi, S. Ghazal (Malaysian Journal of Library and Information Science, 2016)
This paper investigates determinant of continuance intention to use e-book among higher education students. The determinants used in this paper are adopted from Technology Acceptance Model (TAM) and Expectancy Disconfirmation Theory (EDT). The quantitative study employed random sampling where the email invitation which contained a hypertext link of the survey page, enables the participants to access to the survey hosted in Google Drive. Out of 760 sample size, a total of 650 responses were gathered with 509 valid responses used for analysis. The data were analysed to test the relationship between determinants of continuance intention to use e-book among higher education students. The finding demonstrates that determinant of continuance intention to use ebook are based on Satisfaction, while Satisfaction is strongly determined by Perceived Ease of Use and Confirmation of using e-book. Internet self-efficacy is reported to have strong effect on Satisfaction through Perceived Ease of Use, while Perceived Quality affects Satisfaction of using ebook through Confirmation. In general findings from this study are beneficial for libraries in that determinants of continuance intention of using e-books could also be used in selecting and evaluating e-books features before subscription. Additionally e-book vendors could use these findings to improve and enhance features of their e-books services.